Energy deposit by electron excitation in CnN+ projectiles (n=1-3) colliding at in termediate velocity with He atoms : semi-empirical estimates and calculations. Issue 14 (January 2020) - Mahajan, T; Béroff, K; Pons, B; Illescas, C; Chabot, M; Idbarkach, T; Jorge, A; Aguirre, N F; Diaz-Tendero, S
Synopsis: Using measured dissociation branching ratios and theoretical dissociation energies, we extracted semi-empirical estimates of the energy deposit due to electron excitation in Cn N + -He collisions at v=2.2 a.u. We compared these estimates to calculations based on the IAE (Independent Atom and Electron) model where the atom(ion)-atom excitation is treated within the Classical Trajectory Monte Carlo (CTMC) approach. A good agreement has been found. This atomic approach is also able to reproduce the experimental Kinetic Energy Release (KER) in CN + dissociation measured in 3.5 a.u CN + -He collision.